Analisis Capaian Pilar Sosial SDGs Kabupaten Manokwari Tahun 2015 - 2019 - La Ode Alisyah (Lensa Ekonomi, 2022)
This research is entitled Analysis of Achievement of the Social Pillars of SDGs in Manokwari Regency for 2015-2019. The variables used are all indicators, namely the goal without poverty, the goal of zero hunger, the goal of a good health and well-being, the goal of quality education and the goal of gender equality in the social pillars. This study uses descriptive analysis using secondary data on development achievements in 2015-2019 contained in the LKPJ-AMJ document and other official publication documents. The research began by identifying secondary data, then calculating SDGs indicator achievement data for each goal, compared to the achievement targets set out in Presidential Decree Number 59/2017. There are 96 indicators on the Social Pillars, 25% of the indicators that have been implemented and have reached the national target, 31.25% of the indicators that have been implemented and have not reached the national target, 4.17% of the indicators that have not been implemented and have not reached the national target and 39, 58% of indicators for which data is not yet available. Penelitian ini berjudul Analisis Capaian Pilar Sosial SDGs Kabupaten Manokwari Tahun 2015-2019. Varibael yang digunakan adalah seluruh indikator pada yakni tujuan tanpa kemiskinan, tujuan kelaparan, tujuan kehidupan sehat dan sejahtera, tujuan pendidikan berkualitas dan tujuan kesetaraan gender pada pilar sosial. Pada penelitian ini menggunakan analisis deskriptif dengan menggunakan data sekunder capaian pembangunan tahun 2015-2019 yang termuat dalam dokumen LKPJ-AMJ dan dokumen publikasi resmi lainnya. Penelitian diawali dengan mengidentifikasi data sekunder, selanjutnya menghitung data capaian indikator SDGs pada masing-masing tujuan, dibandingkan dengan target capaian yang tertuang dalam Perpres Nomor 59/2017. Terdapat 96 jumlah indikator pada Pilar Sosial, 25% indikator yang sudah dilaksanakan dan sudah mencapai target nasional, 31,25% indikator yang sudah dilaksanakan dan belum mencapai target nasional, 4,17% indikator yang belum dilaksanakan dan belum mencapai target nasional serta 39,58% indikator yang belum tersedia datanya.